PENGELOLAAN PENDIDIK PAUD YANG PROFESIONALISME DI PAUD TAMAN SARI - Dessi Andriani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study aims to determine the management of educators in PAUD TAMAN SARI. This research is a descriptive research with qualitative approach. Subjects in this study were principals, and educators. Data were obtained by interview, observation and document observation. Data analysis used qualitative data analysis technique of interactive model, while data validity by using source and method triangulation. The result of the research shows that the management of educator in PAUD Taman Sari has been running well, through the planning stage, division of task, and the development of competence of educator. The development of the competence of educators PAUD Taman Sari done by attending seminars, workshops, training, tiered training that carried out regularly. Evaluation of the program conducted by PAUD Taman Sari is internally between the principal and the educator, the method used is by way of discussion and also question and answer. Aspects evaluated include the performance of educators. Performance evaluation is done at the end of the school year prior to the new school year